The Economic Impact of the LEADER Program in the Rural Communities of Romania - Ana-Maria Opria; Lucian Roșu; Corneliu Iațu (Scientific Annals of Economics and Business, 2023)
The sustainable development of rural areas is one of the European Union’s objectives. LEADER program contributes to its fulfillment by offering financial support to disadvantaged rural areas. The purpose of this paper is to assess the LEADER program’s economic impact in the Romanian rural communities. Econometric methods of impact assessment were used to analyze the evolution of economic indicators in the beneficiary communities. Propensity Score Matching and Difference in Differences were the methods applied in order to meet the objectives of the paper: analysis of the spatial distribution of projects submitted and funds allocated to LAGs (1), and of the economic evolution of LAG and non-LAG communities, before and after LEADER funding (2). The results indicate a stronger economic growth for the beneficiary rural communities, confirming in all cases the initial hypothesis. LEADER seems to have acted in these directions: the creation of new jobs and increasing the local businesses performance. However, the contribution made was minimal and insignificant. Conclusions of the study highlight that the contribution of the LEADER program to the economic development of rural communities can be at most one of supporting the current level of development, but not of reaching a much higher level. LEADER can be considered, from a quantitative point of view, only an instrument with a positive effect on rural areas, but not an instrument of impact. This is because LEADER did not bring significant changes and didn’t ensure that critical mass that could trigger the economic development of rural communities.